Environmental Noise Sensor Identification System Using Wireless Sensor Networks of (MEMS) Technology (International Journal of Food and Nutritional Sciences, 2023)
This paper presents survey of different nodes of wireless sensor networks which has been made viable by sensing the noise of creature and transmits into the digital frequency. Using micro electro- mechanical systems (MEMS) technology, wireless communications and digital electronics. First, the sensing tasks and the potential sensor networks applications are explored, and a review of factors influencing the design of sensor networks is provided. And we also design the system to identify the creature and his location. Then, the communication architecture for sensor networks is outlined, and the algorithms and protocols developed for each layer in the literature are explored. Open research issues for the realization of sensor networks are also discussed.